35‐2: Development of IGZO UHD In‐Cell Touch Panel LCD for Notebook PC. Issue 1 (28th June 2021) - Kitagawa, Daiji; Miyazawa, Jin; Kikuchi, Tetsuo; Tagawa, Akira; Nishimura, Jun; Tanaka, Noriyuki
Abstract : We have developed the world's first IGZO UHD in‐cell touch panel LCD for Notebook PC (as of December 2020, according to our research). In addition, its four‐sided narrow border feature was achieved by COF mounting and source DeMUX. The touch panel performance has been qualified for mass‐production by internal validation.